2022
DOI: 10.2478/cee-2022-0070
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Precast Concrete Girder Bridge Under Static Load

Abstract: Large-scale construction of transport infrastructure inevitably includes the construction of new bridges. During the design process, many assumptions and simplifications are taken into account. Therefore, the verification of the structural response of new bridges is necessary. One of the possible tests of structural response is a proof-load test which can detect certain problems of investigated structures. The paper introduces numerical and experimental analysis of the new bridge, which is located on Slovak Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Bujnakova P et al verified the effectiveness of the numerical simulation method by comparing the measured data with the numerical simulation results and assessed the precast concrete beam bridges under static loads. The study results showed that this type of girder bridge has good structural properties and can meet the requirements for safe and reliable use under static loads [14]. The literature [15] focused on making construction management decisions and applied hierarchical analysis and expert selection methods to explore them.…”
Section: Introductionmentioning
confidence: 99%
“…Bujnakova P et al verified the effectiveness of the numerical simulation method by comparing the measured data with the numerical simulation results and assessed the precast concrete beam bridges under static loads. The study results showed that this type of girder bridge has good structural properties and can meet the requirements for safe and reliable use under static loads [14]. The literature [15] focused on making construction management decisions and applied hierarchical analysis and expert selection methods to explore them.…”
Section: Introductionmentioning
confidence: 99%